Associação entre oxitetraciclina e cloprostenol no tratamento de vacas leiteiras com retenção de placenta - Fernandes, Carlos Antônio de Carvalho; Palhão, Miller Pereira; Ribeiro, Josiane Rossi; Viana, João Henrique Moreira; Gioso, Marilu Martins; Figueiredo, Ana Cristina Silva; Oba, Eunice [UNESP]; Costa, Deiler Sampaio (Editora Cubo, 2012)
The aims of the present study were to evaluate the incidence rate of retained placental in dairy cows from southern of Minas Gerais and northern of São Paulo State, Brazil; and evaluate the association between oxitetraciclin and cloprostenol on the treatment of animals with retained placenta. For this purpose, 769 pregnant cows were used. After birth, animals diagnosed with retained placenta (n=121) were randomly allocated in two groups. In group I, animals were treated with a single dose of tetraciclin (20mg/ Kg, IM). In group II, the animals received the same antibiotic therapy in group I and an injection of cloprostenol (0.530 mg, IM), a second dose was given 48 hours later. The incidence and degree of endometritis, uterine involution, and the presence of CL were evaluated by vaginoscopy, rectal palpation and ultrasonography, respectively. The intervals between birth and first insemination and between birth and conception and the number of AI per conception were used to evaluate the reproductive performance. Discrete variables were evaluated by Wilcoxon test. The Student “T” test was used to compare means of continuous variables. The overall occurrence of RP was 15.3%. The cloprostenol injections of RP hastened the uterine involution and decreased the occurrence of uterine infection (45% vs 79.49 %), and increased the percentage of animals with corpus luteum between 25 and 40 days after parturition. The intervals from parturition to first artificial insemination (84.44+20.79a vs 74.21+17.74b days) and to conception (149.61+55.82ª vs 121.59+42.41b days) as well as number of AI per conception were reduced (2.65+0.96b vs 3.03+1.29a ) in oxitetraciclin plus cloprostenol treatment. The combination oxytetraciclin and cloprostenol accelerates uterine involution, reduce the occurrence of uterine infections and improves the reproductive performance of dairy cows with retained placenta.

Objetivou-se verificar a ocorrência de retenção de placenta (RP) em vacas leiteiras provenientes de rebanhos leiteiros comerciais da região Sul de MG e Norte de SP, Brasil e avaliar a associação entre oxitetraciclina e cloprostenol para o tratamento de RP. Foram utilizadas 769 vacas gestantes. Após o parto, os animais com RP (N=121) foram aleatoriamente divididos em dois grupos de tratamento: 1) Aplicação de cloridrato de oxitetraciclina, 20 mg/kg (IM) em dose única; 2) inclusão de duas injeções de 0,530 mg de cloprostenol, com 48 horas de intervalo ao tratamento 1. Foram avaliados a ocorrência de infecção, o grau de involução uterina e presença de corpo lúteo aos 25-40 dias pós-parto, por vaginoscopia, palpação retal e ultrassonografia, respectivamente. Também foram comparados o intervalo do parto - 1ª IA, parto/concepção e serviços/concepção. A análise das variáveis discretas utilizou a estatística de Wilcoxon. O teste “T” de Student foi utilizado para comparar variáveis contínuas. A ocorrência de RP foi de 15,7%. A inclusão de cloprostenol ao tratamento acelerou a involução e reduziu a ocorrência de infecção uterina (45% vs 79,49%), e aumentou o percentual de animais com corpo lúteo aos 25-40 dias pós-parto. Os intervalos do parto à primeira inseminação (84,44+20,79a vs 74,21+17,74b ) e do parto à concepção (149,61+55,82ª vs 121,59+42,41b ), e o número de serviços por concepção foram reduzidos (2,65+0,96b vs 3,03+1,29a ) com inclusão do cloprostenol ao tratamento. A associação de antibiótico e cloprostenol acelera a involução uterina, reduz a ocorrência de infecções uterinas e melhora o desempenho reprodutivo das vacas leiteiras com retenção de placenta.
Association between oxytetraciclin and cloprostenol for treatment of retained placenta in dairy cows
Keywords: Reproductive efficiency; Uterine involution; Retained placenta; Eficiência reprodutiva; Involução uterina; Retenção de placenta